1983
DOI: 10.1203/00006450-198305000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zinc Therapy on Lysosomal Inclusion Bodies in Intestinal Epithelial Cells in Acrodermatitis Enteropathica

Abstract: Summary MATERIALS AND METHODSTwo patients with acrodermatitis enteropathica had abnormal lysosornal inclusion bodies in the intestinal epithelial cells while in relapse but fewer smaller ones after zinc therapy. The third patient with acrodermatitis enteropathica in remission on zinc therapy had no inclusion bodies. The smaller inclusion bodies were similar to those found in coeliac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The dermis may show a sparse lymphohistiocytic inflammatory infiltrate. Ultrastructurally, Paneth cells of the intestinal mucosa show inclusions, as well as pleomorphic granules, sometimes becoming confluent, giving rise to giant granules [ 216–218 ]. Some enterocytes contain large lysosomal inclusion bodies [ 216 ].…”
Section: Zinc Homeostasismentioning
confidence: 99%
“…The dermis may show a sparse lymphohistiocytic inflammatory infiltrate. Ultrastructurally, Paneth cells of the intestinal mucosa show inclusions, as well as pleomorphic granules, sometimes becoming confluent, giving rise to giant granules [ 216–218 ]. Some enterocytes contain large lysosomal inclusion bodies [ 216 ].…”
Section: Zinc Homeostasismentioning
confidence: 99%
“…Zinc is known to be essential for normal secretion, granule formation, and the sta biliza tion and release of sec retio n in both Paneths and goblet cells (13,14). The pre sence of abnormal pancreatic ac inar cells ha s been reported in zinc-deficient rat s ( 15), Zinc is probably necessary for normal secretion in all sec retory cells (\ 3).…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies on gut tissue from patients have shown that acrodermatitis enteropathica is associated with cellular abnormalities. Filamentous inclusion bodies in the cytoplasm (Mack et al, 1989;Bohane et al, 1977) and abnormal lysosomal inclusions (Jones et al, 1983) occur in the intestinal Paneth cells of patients. This pathology is considered to be a secondary effect of the disease because it disappears after zinc treatment.…”
Section: Acrodermatitis Enteropathica Acrodermatitis Enteropathica Acmentioning
confidence: 99%